Risk of ischemic stroke in adult patients with congenital heart disease. (25th November 2020) - Giang, K.W; Fedchenko, M; Dellborg, M; Eriksson, P; Rosengren, A; Mandalenakis, Z
Abstract: Introduction: With an increasing proportion of adults with congenital heart disease (CHD) surviving into middle age and beyond, CHD patients will be at increased risk of acquired cardiovascular conditions, such as ischemic stroke. Compared to controls, patients with CHD have a higher prevalence of arrhythmias, persistent shunts enabling paradoxical embolization, heart failure, mechanical valves as well as potentially hypercoagulable states, all of which can further increase the risk of stroke. Purpose: The aim of our study was to investigate the risk of developing ischemic stroke in adults with CHD in Sweden compared to controls from the general population. Methods: We used data from the Swedish National Patient and Cause of Death registries to identify all CHD patients ≥18 years of age, born during the period 1930–1998, with a first time diagnosis of ischemic stroke. Follow-up started in January 1970 and went on until December 2017. Approximately ten controls matched for age and sex were randomly selected from the general population for each patient with CHD. CHD diagnoses were classified into six lesion groups according to a previously published hierarchical classification system. Results: In total, 43, 110 patients with CHD and 474, 267 controls were included in the study (51.4% men) and mean follow up time was 25.4±18.4 years. Patients with CHD had a 6 times higher risk of developing an ischemic stroke compared with controls (hazard ratio 6.0, 95% confidence interval 5.8–6.2, p≤0.001), with altogether 8.8% (n=3785) of CHD patients developing ischemic stroke compared with 1.6% (n=7516) of controls. Ischemic stroke was more common in all CHD lesion groups; however, patients with atrial septal defects/patent foramen ovale had the highest incidence rate of ischemic stroke with an incidence rate of 76.1 events/10, 000 patient years compared with 8.7 in controls. Patients with CHD and ischemic stroke had markedly less hypertension, diabetes mellitus and hypercholesterolemia, compared with controls (7.1%, 2.0%, 2.9% respectively in CHD patients, compared with 19.6%, 6.6%, 5.3%, in controls, p≤0.001 for all). In addition, atrial fibrillation and heart failure were only slightly more common in CHD patients with ischemic stroke compared to controls (atrial fibrillation: 12.0% in CHD vs 10.4% in controls, p=0.01; heart failure: 8.7% in CHD vs 7.3% in controls, p=0.009). Conclusion: In this large nationwide study, we found that the risk of ischemic stroke in adult patients with CHD was six times higher than in controls, despite a lower prevalence of common risk factors for stroke such as hypertension, diabetes mellitus and hypercholesterolemia. In addition, atrial fibrillation and heart failure were only slightly more common in CHD patients compared with controls. This implies that the etiology of ischemic stroke might be different in CHD patients compared with controls. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This work was funded by the Swedish state under an agreement between the Swedish government and county councils, the ALF agreement (Grant number: 236611) and the Swedish Heart-Lung Foundation (Grant Number: 20090724).